(untitled) (Scientific journal of the Fergana State University, 2024)
A lithium hydroxide solution was used to improve the quality of the coating material, and 6 samples of the coating material were taken. Experimental tests were conducted using the method of determining the kinematic viscosity and solidification temperature at temperatures of 20, 40 and 100 °C. In terms of kinematic viscosity and solidification temperature, the SM-4 sample gave the best results compared to the rest of the cast material samples. In terms of flash temperature, the indicator of SM-2 and SM-4 samples gave a higher indicator compared to the rest of the samples. Then, based on the obtained indicators, it was recommended to use SM-2 and SM-4 samples in the fast rotating parts of the equipment.